Innovative teaching: Using multimedia to engage students in interactive learning in higher education - Teoh, Belinda S. P; Neo, Tse Kian (IEEE, 2006)
With the rapid progression in the PC and multimedia technologies, it has become feasible to integrate multimedia technology into the teaching and learning process. What has been the conventional teacher-centred approach is now seeing a shift into one which emphasises on student-centred learning. Traditional educational content can now be transformed into interactive multimedia content by using authoring packages. It has enabled the teacher to innovate his/her instructional design by presenting the educational content in an interactive and multisensory manner rather than the traditional single media format. This infusion of multimedia into teaching and learning has altered instructional strategies in educational institutions. Hence, with the advent of this pervasive information technology, many colleges and universities, including those in Malaysia, are currently gearing their teaching and learning towards one which uses multimedia technology to enhance the student's learning process. With the availability of the devices such as the CD and Internet, in particular the World Wide Web, interactive learning instructions can be delivered to the learners in an asynchronous learning environment. The purpose of the research is to do a comparative study on the impact on student learning when interactive multimedia educational content is delivered to the second year students of the Film & Animation course of Multimedia University via the CD and the Web. A set of instructional materials were developed, implemented an the learners' perception and attitudes towards the use of these multimedia learning instructions recorded. Furthermore, the changing roles and the relationships between the learner and teacher in this interactive learning environment were studied. Therefore, an enhanced model of Gagne's Conditions of Learning was created in the context of interactive learning will be presented in this paper.